Two formulas for consecration the human to divinity - López-Carrasco, Nerea (My University, 2018)
This paper is the study of two formulas for the consecration of the human to the divinity, one in Greek and the other in Latin, regarding to the ambiguity of meaning of the word sacer. I have chosen them, in one hand, because of their similar structures: considering the Greek verb καθιερόω in the first formula as an equivalent of Latin sacer in the second one, the name of the divinity, Hecate and Jupiter respectively, is expressed in dative case. In the other hand, because they show opposite connotations of the word sacer since they belong to different contexts. The first formula in Greek κατεειέρωσεν Σωτίρῃ Ἑκάτῃ is inscribed on a Phrygian epitaph from Timbris (III A.D.) and it aims to consecrate the dead couple to the goddess looking for her protection over them. While the formula in Latin eius caput Iovi sacer esset from Livy’s (III, 55, 7) account of a trial is standing for a curse addressed to the guilty man, sacer to Jupiter. We will see why these formulas are particular individually: syntax of the Greek epitaph is an exception among the others from the same place and time and addressed to Hecate, while the “cursed” consecration addressed to Jupiter, heavenly god not chthonian, is also an anomaly. Finally, I will point out some remarks about the role of Hecate and Jupiter as divinities to which human is consecrated in funerary and judicial context, respectively
Keywords: Griego; Magics; Consecration-formulas; Ancient blessing; Ancient-curse